A single gene codes for the nicotinic acetylcholine receptor alpha-subunit in Torpedo marmorata: structural and developmental implications. - Klarsfeld, A (1984)
We have used Southern blot hybridization to analyze the genomic structure encoding the alpha-subunit of the acetylcholine receptor (AChR) in Torpedo marmorata, with cDNA probes isolated from the electric organ. Four different radiolabelled probes, corresponding to various parts of the alpha-subunit mRNA, hybridized to several genomic fragments of T. marmorata DNA generated by digestion with the restriction enzymes SstI, PvuII and PstI. The same hybridization pattern was observed after washing the blots under low- or high-stringency conditions. As a check for detection sensitivity of heterologous sequences, the same probes were hybridized to PvuII-digested chicken DNA, revealing bands at low stringency which disappeared at higher stringencies. Unambiguously, two of our probes (one of them entirely within the coding region) hybridized to a single genomic fragment from T. marmorata DNA. This feature, as well as the results of an extensive study of the whole hybridization pattern, points towards the uniqueness of alpha-subunit-specific sequences in the genome of T. marmorata. Since overall more bands were found than expected from the cDNA sequence, this alpha-subunit gene must be split by several introns (at least four, possibly more). The length of this gene is at least 20 kb. The existence of a single alpha-subunit gene is consistent with the absence of chemical heterogeneity in the NH2-terminal sequence of the purified alpha-chain, and supports the view that the two alpha-chains belonging to one AChR oligomer have an identical primary structure. It also suggests that localization and stabilization of the AChR in well-defined post-synaptic areas of T. marmorata electric organ basically relies, during development, on 'epigenetic' mechanisms.